The Effect of PBL-based STEAM Approach on The Cognitive and Affective Learning Outcomesof Primary School (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to discover the existence of cognitive and affective learning outcomes of students using Project Based Learning (PBL) - based STEAM (Science, Technology, Engineering, Art, and Mathematics) with scientific learning with inquiry learning models. The type of research was a quasi experimental design. Data were collected by means of test analysis, observation, interviews, and documentation from all fifth grade students of primary school. Data analysis used t-test technique. To discover the effect of PBL-based STEAM approach on cognitive learning outcomes obtained from the pretest-posttest results, while affective learning outcomes were obtained through observation using the measurement data scale in the rubric.The results showed that there were significant differences between the experimental class and the control class on cognitive learning outcomes, however, there were differences in affective learning outcomes. It is expected to strengthen the results of the discussion in the long term to strengthen cognitive and affective learning outcomes.